La consideración ética de la guerra y el uso de la violencia en la España Medieval - Pérez de Tudela Velasco, María Isabel (En la España Medieval, 2007)
The present work seeks to uncover the motives that pushed certain sectors of Hispanic society to rise up against the Islamic dominion recently established on the Iberian Peninsula, the causes within the Islamic community that helped generate a radical clash, and the inevitable search for arguments supporting a resistance that, in the end, ought to be armed.